Nanomechanical DNA resonators for sensing and structural analysis of DNA-ligand complexes - Stefano Stassi; Monica Marini; Marco Allione; Sergei Lopatin; Domenico Marson; Erik Laurini; Sabrina Pricl; Candido Fabrizio Pirri; Carlo Ricciardi; Enzo Di Fabrizio (Nature Communications, 2019)
Intercalating molecules can significantly change the conformation of DNA. Here, the authors fabricated resonators fully composed of DNA forming bundles between microfabricated pillars to study the vibration property of the DNA bundles with/without intercalant molecules.